2009
DOI: 10.11646/zootaxa.2240.1.4
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Lysmata (Crustacea, Decapoda, Hippolytidae) from Venezuela, southeastern Caribbean Sea

Abstract: Lysmata udoi n. sp., a new peppermint shrimp, is described from Venezuela, southeastern Caribbean Sea. All individuals were collected from dens of the toadfish Amphichthys criptocentrus (Valenciennes, 1837) in the subtidal zone. This new species can be distinguished from other closely related species of Lysmata by the number of teeth, length and shape of the rostrum, the relative length of the antennular peduncle, and the number of carpal articles of the second pereiopod. The color pattern is distinctive. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Indeed, previous studies using 16S as a barcode have successfully differentiated among cryptic species complexes in the genus Lysmata , resulting in the description of new species and validation of other species differentiated from one another by minimal but consistent morphological traits (e.g. L. udoi , Baeza et al ., 2009b; L. grabhami versus L. amboinensis , Baeza, 2010a). Studies exploring the feasibility of the mtDNA 16S gene as a barcode in various ornamental crustacean genera (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, previous studies using 16S as a barcode have successfully differentiated among cryptic species complexes in the genus Lysmata , resulting in the description of new species and validation of other species differentiated from one another by minimal but consistent morphological traits (e.g. L. udoi , Baeza et al ., 2009b; L. grabhami versus L. amboinensis , Baeza, 2010a). Studies exploring the feasibility of the mtDNA 16S gene as a barcode in various ornamental crustacean genera (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The first two phylogenetic analyses conducted with peppermint, cleaner, and semiterrestrial shrimps demonstrated that: (1) semiterrestrial shrimps from the genus Merguia represent the sister group to a second natural clade composed by shrimps from the genera Lysmata and Exhippolysmata ; (2) the genus Lysmata is paraphyletic, and includes the genus Exhippolysmata ; (3) the monophyletic clade composed of species of Lysmata and Exhippolysmata can be divided into four well‐supported subclades (Neotropical, Cleaner, Cosmopolitan, and Morphovariable; Baeza et al ., 2009a, b; Baeza, 2010a). A third analysis conducted by Fiedler et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations